2012
DOI: 10.1111/j.1438-8677.2011.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of early chilling stress in two Triticum species: plastic responses and adaptive significance

Abstract: Phenotypic plasticity of two primitive wheat species (Triticum monococcum L. and Triticum dicoccum S.) was studied in response to early chilling stress. Selection pressure differentials, gradients and plasticity costs on plant morphogenesis, growth and reserve carbohydrate consumption were estimated. Regression analysis was applied to investigate differential developmental changes and patterns between treatments. Four-day-old seedlings of T. monococcum and T. dicoccum, differing in plant stature and reserve ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 117 publications
(232 reference statements)
1
29
0
Order By: Relevance
“…7a). Reductions in flag leaf size, total biomass, specific leaf area in wheat have been reported under chilling temperature (4°C) in climate chamber experiment (Valluru et al 2012). Such effects could have been attributed to the direct damage of low temperature on leaves and tissues (Theocharis et al 2012).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…7a). Reductions in flag leaf size, total biomass, specific leaf area in wheat have been reported under chilling temperature (4°C) in climate chamber experiment (Valluru et al 2012). Such effects could have been attributed to the direct damage of low temperature on leaves and tissues (Theocharis et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…), which are associated with a lowered photosynthetic rate (Thakur and Nayyar ), a decrease in shoot biomass, flag leaf size and specific leaf area (Valluru et al. ), and altered carbohydrate metabolism (Theocharis et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of these stressors was variable, but it confirmed the thesis that 'stress memory' and 'cross-tolerance' can be induced in eggplant following the application of stress factors in the early stages of development. Valluru et al (2012) specified morphological changes, i.e. a significant increase in leaf mass ratio, relative growth rate, a reduction in flag leaf size, total biomass and specific leaf area (SLA) as a result of early chilling of wheat.…”
Section: Resultsmentioning
confidence: 99%
“…As these pretreatments triggered an increase in both the fresh and dry weight of roots, it is likely that this enabled developing plants to utilise water and nutrients more effectively. A study by Valluru et al (2012) demonstrated that exposure to early chilling stress during the seedling stage in two Triticum species resulted in adaptive responses, including early flowering, and alterations in several morphological and functional traits. Martínez-Andújar et al (2011) treated tomato seedlings with osmotic stress to improve tolerance to drought and salinity after transplanting.…”
mentioning
confidence: 99%